Assessing the Effectiveness of Case-Based Learning on Students’ Attitudes Toward Chemistry and Formal Reasoning in Acid-Base Topics - Apriyanti, Adelia; Wiyarsi, Antuni (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2024)
Effective teaching strategies are critical in enhancing students’ attitudes toward chemistry and formal reasoning abilities, particularly for complex topics like acids and bases. Case-based learning has emerged as a promising alternative to traditional scientific learning methods. This study aims to compare the differences in attitudes toward chemistry and formal reasoning skills between students exposed to case-based learning and those undergoing scientific learning on acids and bases. A quasi-experimental design with a posttest-only control group was applied to 122 student of 11th grade science students in Yogyakarta, selected using simple random sampling. Data were collected through case-based essay questions and attitude questionnaires. Multivariate analysis (Hotelling’s Trace) assessed the differences between groups. The analysis revealed a significant difference (p = 0.000 < 0.05) in attitudes and formal reasoning skills between the two groups. Students in the case-based learning group demonstrated significantly better attitudes toward chemistry compared to those in the scientific learning group. These findings highlight the potential of case-based learning to enhance students’ engagement and reasoning skills in chemistry. By integrating case-based approaches into acid-base learning, teachers can adopt alternative methods to improve student outcomes. This study underscores the importance of diversifying teaching strategies to address the challenges of complex scientific topics effectively.